DETECTIVE AS A LITERARY GENRE IN THE SYSTEM OF COPYRIGHT OBJECTS OF THE REPUBLIC OF KAZAKHSTAN: PROBLEMS OF DETERMINING THE PROTECTION CAPACITY - Zhalairi , Өмірәлі Шакарапұлы; Amangeldy , Айжан Амангелдіқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article is devoted to the study of the detective as a literary genre as an object of copyright and the problem of criteria of protection. The detective in the Kazakh literature has not been widely distributed, and therefore arouses scientific interest. At the same time, it is the result of creative intellectual activity, the object of copyright. The article analyzes the features of the literary work, presents the points of view of Kazakhstani and foreign authors. However, not every work can be recognized as an object of copyright, in order to be recognized as such, the object must have certain characteristics in order to become protectable. Determining the criteria for the protectability of works is important when recognizing a work as subject to legal protection. The legislation of the Republic of Kazakhstan recognizes creativity and the form of works as such. The article reveals the concepts of purpose, content, dignity, as well as ways and forms of expression of works. The legal literature presents different points of view to the study of the criteria of protectability: creativity, novelty, originality, etc. There is no unity of opinion in foreign practice, in the USA the level of creativity is considered as a criterion. Currently, the concept of determining the lower level of protection capacity, which distinguishes works with an insignificant level of creative character, is increasingly attracting attention. The judicial practice of the Republic of Kazakhstan in dispute resolution adheres to the approach of determining the existence of the creative nature of the work, the Copyright mark, using such tools as an author's expertise for borrowing material and coincidences of creative results. The establishment of criteria for the protection of works is an urgent problem that has a practical nature, and its resolution is necessary in order to determine which works can enjoy copyright protection.